Teologi Injili di Era Postmodernisme - Agustina Pasang (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2020)
The spirit of the Postmodern era is marked by progress in all areas of human life, both technology, science as well as in philosophy, theology and religion. Particulary in the world of theology, the influence of Postmodernism has had a devastating effect on the lives of both believers and the church. This article is a literature review using a reference book that contains discussion of theology, evangelicalism and the Postmodern era by applying descriptive methods. In conclusion, a healthy and consistent theology is a theology that is centered on God and its orientation is from God by God and for God as Paul says in Romans 11:36.